Changes in the Local Government System and Regional Policy in Poland: The Impact of Membership in the European Union - Andrzej Klimczuk; Magdalena Klimczuk-Kochańska (Theoretical Foundations and Discussions on the Reformation Process in Local Governments, 2016)
This chapter presents the successive stages to make changes in the Polish development policy after 1989. The national administration reform of 1990 in the Third Commonwealth of Poland restored the local government after 40 years of non-existence during the time of Polish People's Republic (1944-1989) that was a satellite state of the Soviet Union after the Second World War. Another reform took place in 1998 as a part of preparations for the country's membership in the European Union (EU) from 2004. Currently developed strategic documents are suggesting the use of the "polarization and diffusion model of the development." The authors also discuss the regional policy currently implemented in Poland, which was designed in years 2009-2014. The process of creation of new policy includes plans to reform the policy instruments and to update the strategic framework. Conclusions highlight a need for a clearer division of powers between the center and regional governments and the importance of strengthening the financial basis and institutional capacity building.
Keywords: H77; R58; 330; Cohesion Policy; Horizontal Strategic Framework; Polarization and Diffusion Model; Regional Policy; Transition in Post-communist State